PENGARUH FREQUENT FLYER RELATIONSHIP PROGRAM TERHADAP LOYALITAS PENUMPANG GARUDA INDONESIA (Survei pada member Garuda Frequent Flyer ) - Ramdhani, Kinanti Pra; Gaffar, Vanessa (Universitas Pendidikan Indonesia, 2013)
The tourism industry is the single largest source of foreign exchange that allows for more developed in the future. Tourism enterprises are businesses that provide goods and / or services to meet the needs of tourists and tourism . One is the air transport industry or airlines that meet the needs of tourists. Garuda Indonesia Airlines is one of the commercial airline owned by the government of Indonesia stir in the field of air transport which now serves more than 50 domestic routes and international destinations. Garuda Indonesia Airlines passenger numbers have fluctuated each year experience. Garuda Indonesia Airlines seek to maintain and improve the passenger to use the return of Garuda Indonesia Airlines, as well as the members who have been repeatedly used to be a spiritual eagle so that advocates can recomment it to others. That the higher the level of competition in the industry Airlines, makes the management realized that needs a strategy to reach the target customer loyalty. To improve passenger loyalty, one of the programs conducted by Garuda Indonesia Airlines is the Frequent Flyer Relationship Programs at Garuda Indonesia to enhance member loyalty. The purpose of this study was to obtain an overview of frequent flyer program relationship, loyalty and the effect relationship freqeunt flyer loyalty program. This type of study is a descriptive verifikatif and methods used are probability sampling with random sampling technique sistematic and the number of respondents that as many as 100 respondents Garuda frequent flyer member. Data analysis technique used is a tool path analysis with SPSS 18.0 computer software, interviews and distributing questionnaires as data collection techniques. The study findings suggest that, frequent flyer program relationship with the dimensions used are benefits, interest, greeted personally, and prestige have high impact on member loyalty Garuda Indonesia Airlines. Dimensions of relationship-forming frequent flyer program that has the benefit of high influence. As for advice to companies is to maximize the Garuda Frequent flyer programs and services in order to improve and maintain member loyalty in Garuda Indonesia Airlines.